Hyperuricaemia and gout: time for a new staging system?. Issue 9 (9th April 2014) - Dalbeth, Nicola; Stamp, Lisa
Abstract : The current widely used clinical staging system for hyperuricaemia and gout describes the symptomatology of gout, but does not capture key aspects of the pathological basis of the disease. We propose a new clinical staging system. Stage A: hyperuricaemia, but without evidence of monosodium urate (MSU) crystal deposition or symptoms of gout. Stage B: MSU crystal deposition by microscopy or advanced imaging, but without signs or symptoms of gout. Stage C: MSU crystal deposition with prior or current symptoms of acute gout flares. Stage D: advanced gout requiring specialist interventions. This proposed new staging system provides a clear focus on gout as a chronic disease of MSU crystal deposition, and provides a rational framework to test the role of screening and treatment of asymptomatic disease.